2000
DOI: 10.1016/s0378-5955(00)00026-5
|View full text |Cite
|
Sign up to set email alerts
|

Otolith regularities

Abstract: The masses and the area sizes of the otoliths for the utriculus, sacculus and lagena of 15 species of the Black Sea fish are analyzed. Morphometrical otolith regularities are derived and their functional and ecomorphological explanations are suggested. The otolith regularities are summarized in four otolith rules: (1) the masses of the otoliths gradually increase with the fish growth. (2) The mass ratio of the sacculus and utriculus or the sacculus and lagena otoliths does not change with the fish growth. (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 55 publications
3
99
1
Order By: Relevance
“…To simulate the mechanics of CO 2 -altered otoliths, we applied the size and relative density data from sagittal otoliths in our experiment to a mathematical model of otolith motion in response to an 0.8-nm amplitude sinusoidal acoustic wave (27,28). Our simulation demonstrated that when subjected to the same sound stimulus, the estimated CO 2 -driven increase in relative otolith mass results in an increased displacement amplitude compared with control otoliths (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…To simulate the mechanics of CO 2 -altered otoliths, we applied the size and relative density data from sagittal otoliths in our experiment to a mathematical model of otolith motion in response to an 0.8-nm amplitude sinusoidal acoustic wave (27,28). Our simulation demonstrated that when subjected to the same sound stimulus, the estimated CO 2 -driven increase in relative otolith mass results in an increased displacement amplitude compared with control otoliths (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Alteration of otolith size, density, and mass has direct impacts on otolith mechanics and influences sensory function (27)(28)(29). To simulate the mechanics of CO 2 -altered otoliths, we applied the size and relative density data from sagittal otoliths in our experiment to a mathematical model of otolith motion in response to an 0.8-nm amplitude sinusoidal acoustic wave (27,28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These "ear rocks" are initially dome-like in structure (Fig. 1D), but will, with age, take on complex shapes consistent with the shape of the underlying sensory maculae, and with the biophysical requirements of each maculae for the sensing of motion and sound (Das, 1994;Lychakov and Rebane, 2000). Otolith formation begins with the aggregation of free-floating protein core particles, identifiable at 18-20 h post-fertilization (hpf).…”
Section: Structure and Development Of The Otoconial And Otolithic Memmentioning
confidence: 99%